2015
DOI: 10.1002/qre.1867
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Model for Electronic Devices under Time Varying Voltage

Abstract: Present reliability models, which estimate the lifetime of electronic devices, work under the assumption that the voltage level must be constant when an Accelerated Life Testing is performed. Nevertheless, in a real operational environment, electronic devices are subjected to electrical variations present in the power lines; that means the voltage has a time-varying behavior, which breaks the assumption of reliability models. Thus, in this paper, a reliability model is presented, which describes the lifetime o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Many works are found to attempt the problems on reliability optimization using GA, PSO, ABC algorithms and other heuristic algorithms. Again, in most of the works, the component reliabilities are of constant values and only few (Mori and Ellingwood, 1993;Me ´ndez et al 2015;Mourelatos et al 2015;Wang et al 2015;Zhu and Zhifu 2016;Ahmadivala et al 2019;Zafar and Wang 2020) are seen to consider these as time dependent functions. However, the component reliabilities should be time dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Many works are found to attempt the problems on reliability optimization using GA, PSO, ABC algorithms and other heuristic algorithms. Again, in most of the works, the component reliabilities are of constant values and only few (Mori and Ellingwood, 1993;Me ´ndez et al 2015;Mourelatos et al 2015;Wang et al 2015;Zhu and Zhifu 2016;Ahmadivala et al 2019;Zafar and Wang 2020) are seen to consider these as time dependent functions. However, the component reliabilities should be time dependent.…”
Section: Introductionmentioning
confidence: 99%
“…These criteria must be able to consider the reliability during the component's lifetime. For this purpose, Mean‐Time‐To‐Failure ( MTTF ) which is defined as the integration of reliability curve from zero to infinity, might serve as an appropriate criterion for such reliability problems …”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Silva et al 1 and Cordeiro et al [14][15][16] investigated and defined statistical properties of the BWD. Application of BWD in reliability analysis can be found in Silva et al, 1 Hazra et al, 17 and Méndez et al 18 Other field applications of BWD can be found in Carrasco et al, 6 Sigla et al, 19 Mahmoud and Mandouh, 20 and Sun. 21 In this paper, we propose a reliability analysis by using the BWD and the inverse power law (IPL) to describe the lifetime and performance of ED with a nonmonotone failure rate.…”
Section: Introductionmentioning
confidence: 99%